f(x)+g(x)
= -5x - 4 + 6x - 7
= .....
let f(x)=-5x-4 and g(x)=6x-7. find f(x)+g(x)
16 answers
f(x)+ g(x)=(-5x-4)+(6x-7)
= x-11
= x-11
1. x-11
2. -3x + 9
3. -30x^2 + 28x - 6; all real numbers
4. x-4; all real numbers except x = -4
5. It doesn't matter which discount is applied first, the result is the same
2. -3x + 9
3. -30x^2 + 28x - 6; all real numbers
4. x-4; all real numbers except x = -4
5. It doesn't matter which discount is applied first, the result is the same
@Trust me I'm right 100%, answers are correct.
D
B
C
D
C
D
B
C
D
C
Thanks for this you guys! Remember, it's not cheating if you're not caught!
Hailey is right 100%
respect
Hailey and Trust me I’m right 100% are both right for Jan. 2022
Thank-you!!
"Trust me I'm right 100%" and "Hailey" are both actual life savers thank you.
100% correct tysm!!
literal swag gaming. shoutout to trustmeimright
Thank you Hailey and Trust me!!!
Hailey is right. I got 100%
The "trust me I'm right 100%" boi is spot on (well-done homie)
Got 2/5
Correct:
1. x - 11
2. -3x + 9
3. 11
4. -30x^2 + 28x - 6; all real numbers
5. x - 4; all real numbers except x ≠ -4
Correct:
1. x - 11
2. -3x + 9
3. 11
4. -30x^2 + 28x - 6; all real numbers
5. x - 4; all real numbers except x ≠ -4